The great Boston molasses flood - Crandall, William, 1956- (SAGE knowledge. Cases., 2016)
This case discusses the Great Boston Molasses Flood of 1919, when a storage tanker split, releasing two million gallons of the liquid. Over twenty people were killed and hundreds of others injured in the disaster and it prompted a review of regulation concerning construction in the city.